IMPLEMENTATION OF SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN REALIZING A VILLAGE WITHOUT POVERTY IN SUGIHWARAS VILLAGE, CANDI DISTRICT, SIDOARJO REGENCY - Ikhma, Akhfania; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of the Sustainable Development Goals (SDGs) in realizing a Poverty-Free Village in Sugihwaras Village, Candi District, Sidoarjo Regency, with a specific focus on the Village Fund BLT program as part of the SDGs for Villages Without Poverty. Method: A qualitative descriptive approach was employed, examining four key dimensions of implementation—communication, resources, disposition, and bureaucratic structure—through in-depth interviews, observations, and documentation with key informants including the Village Head and implementing officials. Results: The findings indicate that the implementation of the program has been carried out effectively across all four dimensions. Communication is transparent through village deliberations, human resources and facilities are adequate, implementers demonstrate strong commitment, and the bureaucratic structure functions well through clear task division and structured SOPs. Novelty: The research provides a contextual contribution by highlighting how poverty alleviation policies at the village level can be successfully executed through integrated governance, offering a replicable model for other villages in achieving SDGs, and strengthening local governance as a foundation for sustainable development.